FEATURES OF PSYCHODYNAMICS AND INDIVIDUAL STYLE OF ACTIVITY OF HIGHLY QUALIFIED BOXERS IN COMPETITION CONDITIONS - Kadamov S.; Raximboyev F. (Web of Journals Publishing, 2024)
This Article Presents the Results of Research on the Properties of the Nervous System of Highly Qualified Boxers, Analyzes the Patterns of Connections Between Psychophysiological Characteristics and The Individual Style of Activity of Boxers.
Keywords: Psychophysiological characteristics, Nervous system properties, Boxing athletes, Individual activity style, Psychodynamics, Training methodology, Physical and mental qualities, Sports results, Extreme conditions, Typological features.